Influence of CTAB surfactant on the phase, morphology, light absorption and photocatalytic performance of BiOF nanomaterials. (18th September 2019) - Yan, Aihua; Feng, Hao; Hu, Miao; Huang, Fei; Jin, Tianxu; Liu, Yingdan; Li, Qi; Qiang, Yinghuai
Abstract: Bismuth oxyhalide (BiOX, X = F, Cl, Br, I) semiconductors exhibit excellent optoelectronic properties due to their special layered structure. However, the understanding of BiOX-based alloys and hybrids still keeps lacking. Here, BiOBr/BiOF hybrids were in situ synthesized by a facile hydrothermal method under the aid of cetyltrimethylammonium bromide (CTAB) surfactant. The influence of CTAB on the phase, morphology, light absorption and photocatalytic performance was investigated in detail. The results showed that the morphology gradually evolved from irregular microblock to nanoplate, and the band gap was obviously narrowed from 3.66 to 2.69 eV with the increase of CTAB. Importantly, BiOBr/BiOF hybrids markedly enhanced the light absorption and photocatalytic performance. The degradation efficiency towards methylene blue (MB) arrived at 93.2% within 80 min under UV–vis light irradiation, to be about three times higher than that of pure BiOF with 32.7% degradation efficiency. This work may provide a deep understanding for BiOX hybrids.